Attractants for swine starter feeds: aroma vs. taste - B A Koch; G L Allee; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1975)
Duroc weaned pigs given a choice of feed containing an aromatic or sugar chose diets containing 5% sugar. The preference pattern was altered by pre-weaning feeding in that pigs tended to consume the initial ration. However, they later exhibited a preference for the sugar diet indicating that taste was more of an attractant than aroma. Pigs with access to only one diet consumed approximately the same amount of feed per day, so weight gains and feed/gain ratios were similar. Neither aroma nor sugar increased feed intake or performance by pigs offered only one diet.; Swine Day, Manhattan, KS, November 13, 1975
Keywords: Swine day; 1975; Kansas Agricultural Experiment Station contribution; no. 505; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 283; Swine; Aroma vs. Taste; Weight gain; Feed/gain ratio